2022
DOI: 10.1016/j.yebeh.2021.108429
|View full text |Cite
|
Sign up to set email alerts
|

Indirect treatment comparison of cenobamate to other ASMs for the treatment of uncontrolled focal seizures

Abstract: Objective: The efficacy and safety of cenobamate relative to other antiseizure medications (ASMs) has not been evaluated. An indirect treatment comparison (network meta-analysis) was performed to determine if adjunctive cenobamate increases the odds ratio (OR) for 50% responder rate or for withdrawals due to treatment-emergent adverse events (TEAEs) leading to ASM discontinuation versus adjunctive therapy with other ASMs. Methods: A systematic literature review was conducted to identify randomized, double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…However, in a recently published meta‐analysis, it was concluded that cenobamate was associated with a higher responder rate and a better likelihood of providing seizure freedom compared to brivaracetam, eslicarbazepine acetate, lacosamide, and perampanel 17 . The superiority of cenobamate for seizure reduction was reported in a recent review that showed that FDA‐recommended maintenance doses nearly doubled the chances of ≥50% seizure reduction and found that the tolerability profile of cenobamate was consistent with other ASMs in its class 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recently published meta‐analysis, it was concluded that cenobamate was associated with a higher responder rate and a better likelihood of providing seizure freedom compared to brivaracetam, eslicarbazepine acetate, lacosamide, and perampanel 17 . The superiority of cenobamate for seizure reduction was reported in a recent review that showed that FDA‐recommended maintenance doses nearly doubled the chances of ≥50% seizure reduction and found that the tolerability profile of cenobamate was consistent with other ASMs in its class 18 …”
Section: Discussionmentioning
confidence: 99%
“…17 The superiority of cenobamate for seizure reduction was reported in a recent review that showed that FDA-recommended maintenance doses nearly doubled the chances of ≥50% seizure reduction and found that the tolerability profile of cenobamate was consistent with other ASMs in its class. 18 Interactions occurring between concomitant ASMs with varying mechanisms of action may lead to tolerability issues that affect patient compliance. Cenobamate acts as a CYP2C19 inhibitor, significantly increasing exposure to concomitant phenytoin or phenobarbital therapies when used as adjunctive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher lipophilicity leads to unnecessary nonspecific partitioning into brain tissue 32,33 . In two recent indirect comparisons of ASM efficacy in patients with focal seizures, 34,35 the relative responder rate was highest for molecules with TPSA value > 90 (Figure 2). The exact nature of the nonspecific drug disposition sites within epileptogenic brain tissue requires further investigation.…”
Section: Marketed Asms Are More Polar Than Other Cns Drugsmentioning
confidence: 99%
“…Correlation between the topological polar surface area (TSPA) of antiseizure medications and the odds ratio versus placebo for reduction of seizure frequency in patients with focal seizures. Values are based on data from Privitera et al (A,B) 35 and Lattanzi et al (C) 34 . (A,B) Correlation between the TPSA of antiseizure medications and ≥50% responder rate across all studied doses (A) or the ≥50% responder rate at maximal dose in each study (B) 35 .…”
Section: Marketed Asms Are More Polar Than Other Cns Drugsmentioning
confidence: 99%
See 1 more Smart Citation